(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Political representation of women is seen as an important factor in all aspects of progress; however India’s policies on gender equality continue to be scrutinized. After independence in 1947, a number of measures were undertaken to strengthen women’s political presence in the numerous local government structures in India through decentralizing authority. The Panchayati Raj Institutions has enhanced the involvement in decision-making role in policy institutions by disadvantaged sectors of society, including women. Therefore, by the application of quality approaches, such as paper analyses of the amendment act of the Panchayati Raj institutions and expert interviews with electing woman members of a single Keralan district, this research seeks to examine women’s political leadership within the local government institutions. This paper aims to recognize the problems facing women in roles of political leadership in India, the largest democratic country. Study findings show that significant progress is being made in the role of leadership on women’s empowerment but that there are still some key barriers to women being involved in the policy sphere.